Pedagogical Ideas of Domestic Researchers in the Context of the Legacy of Vasily Sukhomlynskyi - Zavgorodnia, Tetiana; Strazhnikova, Inna (Pedagogical Discourse, 2017)
Using the comparative analysis of pedagogical ideas of V.О. Sukhomlynskogo and modern Ukrainian scientists from different industries of pedagogics, their tangencies and divergence of positions are certain in the article. On the basis of historiography analysis of pedagogical ideas of the prominent Ukrainian teacher, applying the komporativistic method of research comparison of ideas of teacher is conducted with position to concrete positions of the Ukrainian researchers, their actuality is well-proven for pedagogical science in general and modern formation of Ukraine in particular. Generalizing work of home researchers in illumination of problems that actualized in the pedagogical inheritance of . V.О. Sukhomlynskogo, it is set that consonant are ideas of maintenance of national education, selection of ways of realization of him in practical activity; problems of preparation of the teacher, development of his work, professionalism, pedagogical mastery (possessing a pedagogical technique, broadcasting); ideas of education of personality in a collective and determination of signs of educative collective; Defending of idea is about an interconditionality and interdependence of development of collective and development of personality; problems of domestic education, development of theory of paternal pedagogics.Also other problems of pedagogical inheritance of V. Sukhomlynskogo examined by home scientists in the context of calls of contemporaneity. question of labour pedagogics; modern look to socialization of student young people; retrospective analysis of pedagogical looks of V.О. Sukhomlynskogo and K.D. Ushynskogo (M.Y.Antonets, L.S. Bondar, T.V. Hryn and other) and others like that. Key words: V.О. Sukhomlynskyi, home researchers, komporativistic approach, historiography of research, consonantness of pedagogical ideas, preparation of the teacher, national education, educative collective, domestic education, paternal pedagogics.